(untitled) (Nativa, 2024)
O objetivo do trabalho foi avaliar o desempenho do milho cultivado com diferentes doses de dejeto líquido suíno (DLS), comparado à adubação mineral (NPK) e sem adubação. Foram avaliadas quatros doses de DLS a partir da necessidade da cultura (50%, 100%, 150% e 200%), NPK e sem adubação (testemunha), com cinco repetições para cada tratamento, com delineamento de blocos casualizados em condições de campo. Foram determinadas a produção de matéria seca total (MST), colmos (MSC) e folhas (MSF), os componentes de produtividade comprimento de espigas (CE), número de fileiras de grãos por espiga (NFGE), número de grãos por espiga (NGE) e número de espigas por metro quadrado (NEMQ), a produtividade de grãos (PG) e o índice de colheita (IC) do milho. As doses de 100%, 150% e 200% de DLS se equipararam ao NPK, tanto para produção de MST (média 6.077 kg/ha), quanto para MSC (4.000 kg/ha) e MSF (2.076 kg/ha). O milho fertilizado com 50% de DLS apresentou maior NEMQ (23) se comparado à testemunha (19) e não houve diferença significativa entre as doses de DLS e NPK (média 20,9). A dose 200% DLS se equiparou ao tratamento NPK no NGE (média 412), no NFGE (12,1) e PG (12.674 kg/ha). As doses de DLS 50, 100 e 150% da recomendada não são equivalentes à adubação NPK, reduzindo, respectivamente, 175, 115 e 114% a PG. Palavras-chave: Zea mays; adubação orgânica; dejetos de animais; eficiência adubação. Pig slurry doses affect plant growth and corn grain yield ABSTRACT: The aim was to evaluate the performance of corn grown with different doses of pig slurry (PS), compared to mineral fertilization (NPK) and without fertilization. Four doses of PS were evaluated from the need of the crop (50%, 100%, 150% and 200%), NPK and without fertilization (control), five replications each treatment, with a randomized block design under field conditions. The production of total dry matter (DM), stems (DMS) and leaves (DML), yield components ear length (EL), number of rows of grains per ear (NRGE), number of grains per ear (NGE) and number of ears per square meter (NESM), grain yield (GY) and corn harvest index. The doses of 100%, 150% and 200% of PS were equivalent to NPK, both for DM production (mean 6,077 kg/ha), and for DMS (4,000 kg/ha) and DML (2,076 kg/ha). Corn fertilized with 50% PS showed higher NESM (23) compared to the control (19) and there was no significant difference between the doses of PS and NPK (mean 20.9). The 200% PS dose matched the NPK treatment in NGE (mean 412), NRGE (12.1) and GY (12,674 kg/ha). The PS doses of 50, 100 and 150% of the recommended are not equivalent to NPK fertilization, reducing, respectively, 175, 115 and 114% of GY. Keywords: Zea mays; organic fertilization; animal manure; fertilization efficiency.